Mistrust in government and National Health Insurance: A qualitative study of solo private practitioners in Cape Town - Bridget L. Perrow; Helen Schneider (South African Family Practice, 2023)
Background: The participation of independent private general practitioners (GPs) is of fundamental importance to the successful implementation of key elements of the proposed National Health Insurance (NHI) reform, notably the contracting units for primary health care (CUPS). This study explored knowledge and perceptions of the NHI reforms of private GPs following the tabling of the NHI Bill in parliament in 2019.